Pelatihan SPSS Pada Mahasiswa Pendidikan Ekonomi Untuk Mendukung Penguatan Keterampilan Literasi Numerasi Digital - Rahman Rahman; Kharisma Nugraha Putra; Grace Evelina Buji; Eriawaty Eriawaty; Fendy Hariatama (Universitas Negeri Surabaya, 2025)
This Community Service activity aims to provide students with a deep understanding of statistical data processing. The problem that is often found in economic education students at the Faculty of Teacher Training and Education, Palangka Raya University is that there are still students who do not understand statistical testing. So it is necessary to provide training in the Statistical Product for Service Solutions program. This Statistical Product for Service Solutions training activity provides significant benefits for students. Starting from the material presentation stage, training in the use of SPSS, data analysis exercises and evaluation of these training activities where students gain a deep understanding of the concepts in statistical tests and the use of statistical test applications used. Of course, it can be seen in the evaluation that each trainee can understand the material provided and be able to apply it. The results obtained from this activity are that the participants who take part not only get theoretical benefits but also practical benefits as a process of managing and analyzing data that requires using statistics.